2009
DOI: 10.1037/a0017727
|View full text |Cite
|
Sign up to set email alerts
|

Agreeableness and alcohol-related aggression: The mediating effect of trait aggressivity.

Abstract: This study investigated the mediating effect of trait aggressivity on the relation between agreeableness and alcohol-related aggression in a laboratory setting. Participants were 116 healthy male social drinkers between 21 and 30 years of age. Agreeableness and trait aggressivity were measured using the Big Five Inventory and the Buss-Perry Aggression Questionnaire, respectively. Following the consumption of an alcohol or no-alcohol control beverage, participants completed a modified version of the Taylor Aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 96 publications
1
19
0
Order By: Relevance
“…Accordingly, these cold and quarrelsome personalities tend to exhibit more aggressive characteristics than their agreeable counterparts (Gleason, Jensen-Campbell, & Richardson, 2004;Laursen, Pulkkinen, & Adams, 2002;Miller, Parrott, & Giancola, 2009;Skeem, Miller, Mulvey, Tiemann, & Monahan, 2005). Consistent with the GMA, researchers have discovered that antagonistic individuals have a biased tendency toward aggressive responses when exposed to threat-relevant information (e.g., Graziano, Jensen-Campbell, & Hair, 1996;Leonard, Quigley, & Collins, 2003;.…”
mentioning
confidence: 77%
“…Accordingly, these cold and quarrelsome personalities tend to exhibit more aggressive characteristics than their agreeable counterparts (Gleason, Jensen-Campbell, & Richardson, 2004;Laursen, Pulkkinen, & Adams, 2002;Miller, Parrott, & Giancola, 2009;Skeem, Miller, Mulvey, Tiemann, & Monahan, 2005). Consistent with the GMA, researchers have discovered that antagonistic individuals have a biased tendency toward aggressive responses when exposed to threat-relevant information (e.g., Graziano, Jensen-Campbell, & Hair, 1996;Leonard, Quigley, & Collins, 2003;.…”
mentioning
confidence: 77%
“…It is unknown how prevalent this effect would be in a broader population, a sample of subjects with a history of alcohol-related violence, or a sample comprised of only individuals with a history of alcohol abuse and dependence. One strategy for future work may be the selection of a sample with a history of trait aggression which may enhance the results as previous studies have shown that high trait aggression is a predictor of alcohol-related aggressive behavior (Miller et al 2009). …”
Section: Discussionmentioning
confidence: 97%
“…Although this is not critical for a resting-state experiment where subjects are asked to do nothing than rest motionless with their eyes closed, we cannot rule out the existence of psychological expectancy effects on 1 day and not the other. Moreover, we did not collect specific personality, impulsivity or cognitive measures that could account for alcohol having diverging effects on different individuals (Dougherty et al, 2004;Miller et al, 2009), independently of their drinking history.…”
Section: Discussionmentioning
confidence: 99%
“…For example, impairment of connectivity in the so-called self-referential RSN could portend increased impulsivity (Dougherty et al, 2000(Dougherty et al, , 2008 and even aggressive behavior to intoxicated persons (Giancola, 2002a,b;Miller et al, 2009). In addition, neurocognitive disruption by acute alcohol administration might be manifested with disrupted connectivity in some other fronto-cortical networks (see, e.g., Rzepecki-Smith et al, 2009).…”
Section: Introductionmentioning
confidence: 99%